2021
DOI: 10.1177/08862605211016344
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the Public’s Health Through Successful Reentry for Sex Offender After Incarceration

Abstract: This paper describes the post-incarceration reintegration experiences of military veterans convicted of sex offenses and identify potential interventions to ease reintegration for this population. Participants were a convenience sample of 14 veterans who were on sex offender (SO) registries and 21 community stakeholders involved in supporting persons during re-entry. Subjects were identified purposively and through snowball sampling, in Massachusetts. We employed semi-structured qualitative interviews of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In addition, many community agencies that partner for housing services with the VA have exclusion policies that prevent serving those with sexual offense histories. These include the U.S. Department of Housing and Urban Development as well as Grant and Per Diem community partnerships with nonprofits offering transitional housing (Simmons et al, 2018; Sreenivasan et al, 2019).…”
Section: The Present Studymentioning
confidence: 99%
“…In addition, many community agencies that partner for housing services with the VA have exclusion policies that prevent serving those with sexual offense histories. These include the U.S. Department of Housing and Urban Development as well as Grant and Per Diem community partnerships with nonprofits offering transitional housing (Simmons et al, 2018; Sreenivasan et al, 2019).…”
Section: The Present Studymentioning
confidence: 99%
“…Providing treatment to manage deviant sexual impulses among veterans with sexual offenses is an important target for risk reduction and successful community reintegration not offered by the VA. Simmons et al (2018) identified access to sex offender treatment as an important facilitator for community reentry. Specifically, military veterans with sexual offenses identified a need to have access to sex offender-specific treatment that would help to address their sexual impulses.…”
Section: Upstream Va Policy Shiftmentioning
confidence: 99%
“…These public attitudes not only affect the well-being of people with sexual convictions due to internalized stigma ( Tewksbury, 2012 ), they also influence legislation and policies, such as the implementation of sex offender registries and residency restrictions ( Kernsmith et al, 2009 ; Mancini et al, 2010 ), therapeutic efficacy ( Beech & Hamilton-Giachritsis, 2005 ), public vigilantism ( Cubellis et al, 2019 ), jury decisions ( Vidmar, 1997 ), and the successful societal reintegration of people with sexual convictions ( Clark, 2007 ; Willis et al, 2010 ). Further, it has been argued that problems in each of the above can increase the likelihood of recidivism ( Freeman, 2012 ; Simmons et al, 2021 ). Thus, it is important that these negative attitudes are understood more deeply.…”
Section: Introductionmentioning
confidence: 99%